2021
DOI: 10.1002/pon.5691
|View full text |Cite
|
Sign up to set email alerts
|

Symptom distress and quality of life among Black Americans with cancer and their family caregivers

Abstract: Objective Black Americans are disproportionately affected by cancer and chronic diseases. Black patients with cancer and their family caregivers may concurrently experience symptoms that influence their wellbeing. This study investigates the influence of mental and physical symptom distress on quality of life (QOL) among Black Americans with cancer and their family caregivers from a dyadic perspective. Methods One hundred and fifty‐one dyads comprised of a Black American with breast, colorectal, lung or prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…These networks included breast oncologists, community engagement specialists, nurses, psychologists, and faculty members. Additional efforts were made to recruit partners who identified as Black/African American, a group that is historically underrepresented in the partner-focused psychosocial oncology research [39][40][41].…”
Section: Recruitment and Enrollmentmentioning
confidence: 99%
“…These networks included breast oncologists, community engagement specialists, nurses, psychologists, and faculty members. Additional efforts were made to recruit partners who identified as Black/African American, a group that is historically underrepresented in the partner-focused psychosocial oncology research [39][40][41].…”
Section: Recruitment and Enrollmentmentioning
confidence: 99%
“…2 , 3 Physical discomfort, fatigue, sleep problems, overload, and mental distress are the main problems reported by patients with cancer and their family caregivers. 4 , 5 In addition, primary caregivers are frustrated by the high caregiving burden, lack of independence and freedom, and the need, at times, to hide their depression symptoms. 6 Negative emotions are infectious to make cancer dyads suffer more.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that family caregivers of advanced cancer patients with high symptom severity and care dependency perceive a lower QoL. The literature emphasised that cancer patients experience fatigue, sleep problems, pain, and mental problems the most and that these disturbing symptoms also affect their family caregivers and reduce their QoL (Ellis et al, 2021; Wen et al, 2019). Seeing their loved ones suffer and depend on others due to symptoms causes great sadness in the family caregivers, and they may feel guilty for not being able to alleviate the symptoms of their patients, and this may be reflected in their QoL (Stamataki et al, 2014).…”
Section: Discussionmentioning
confidence: 83%